Mortality among patients undergoing orthopedic surgeries and admitted to the ICU - Assaggaf, Hussein; Alrashed, Fahad Ahmed; Alsaluli, Mansour Musaad; Alghamdi, Hussain Saeed; Alghamdi, Mohammed Saleh; Alrabie, Muteb Saad; Alasmari, Abdulrahman Hassan; Alsulaimani, Abdullah Naif; Nasser, Ahmed Essam; Bukhari, Nada Abdulqader; Alzaidi, Abdullah Abdulaziz (International Journal Of Community Medicine And Public Health, 2021)
Many postoperative complications have been associated with orthopedic surgeries, which require patients to be admitted to intensive care units. In this study, we reviewed previous studies that reported the mortality rates for patients undergoing orthopedic surgeries and have been admitted to the ICU, in addition to discussing the risk factors and complications for this event and the possible preventive measures. Studies showed that mortality rates in the ICU following orthopedic procedures are much lower than other procedures that are usually associated with higher rates of complications and deaths. However, serious efforts should be offered to decrease the development of complications that may increase the burdens of such cases. To achieve this, the identification of the possible risk factors is essential for decreasing this burden. We found that old age, the presence of comorbidities, the complexity of the procedure, and having large amounts of blood transfusion before the procedure might be significant factors for the development of severe complications and subsequent death. We have also discussed some complications like cardiovascular, cerebral, spinal, pulmonary, and renal disorders. Eliminating these disorders would require more effort for eliminating pain, applying appropriate doses of anesthetics, antibiotics, and beta-blockers.